2010
DOI: 10.1029/2010jb007566
|View full text |Cite
|
Sign up to set email alerts
|

Modeling short‐ and long‐term slow slip events in the seismic cycles of large subduction earthquakes

Abstract: [1] Slow slip events (SSEs) occur in the deeper extents of areas where large interplate earthquakes are expected in subduction zones, such as the Nankai region of Japan and the Cascadia region of North America. In the Nankai region, SSEs are divided into long-and short-term SSEs, depending on their duration and recurrence interval. We modeled and examined the occurrence of long-and short-term SSEs and changes in their behavior during the seismic cycles of large interplate earthquakes. In these numerical simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
132
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(138 citation statements)
references
References 59 publications
5
132
1
Order By: Relevance
“…A more similar case was found in the Alaska subduction zone, where long-term SSEs with duration of several years were observed downdip to the source region of the 1964 M 9.2 Alaska earthquake 22 . Therefore, we can consider the southern source to be a phenomenon like a longterm SSE, but this would have a total duration of about 9 years, longer than any long-term SSE reported previously; thus, we refer to it as a very long-term transient event, following the terminology in simulation studies 23,24 .…”
Section: Resultsmentioning
confidence: 99%
“…A more similar case was found in the Alaska subduction zone, where long-term SSEs with duration of several years were observed downdip to the source region of the 1964 M 9.2 Alaska earthquake 22 . Therefore, we can consider the southern source to be a phenomenon like a longterm SSE, but this would have a total duration of about 9 years, longer than any long-term SSE reported previously; thus, we refer to it as a very long-term transient event, following the terminology in simulation studies 23,24 .…”
Section: Resultsmentioning
confidence: 99%
“…In the Nankai subduction zone, seismogenic faults at depths of 5-25 km are strongly locked, although locking at the transition zone at depths of 25-35 km, where short-term SSEs and nonvolcanic DLF tremors are located, is weaker than at shallow depths (Tabei et al, 2007). A simulation study revealed that the recurrence interval of short-term SSEs becomes short as the occurrence of a great earthquake becomes imminent (Matsuzawa et al, 2010). Monitoring these events is therefore important to elucidate the seismogenic processes related to great earthquakes at the Nankai Trough.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have mainly focused on reproducing the slip distributions, rupture segmentations, and recurrence intervals of historical earthquakes, based on realistic fault models and subduction zone structures obtained from seismic surveys. In contrast, simulations based on simplified fault models can provide us with insights into earthquake rupture patterns, cycles, and related phenomena such as slow slip events (SSEs) (e.g., Matsuzawa et al 2010;Noda et al 2013Noda et al , 2014Ariyoshi et al 2014). Hori and Miyazaki (2011) simulated occurrences of M7-8 earthquakes during M9 earthquake cycles to reproduce the occurrence of the 1978 M w 7.5 earthquake that occurred offshore Miyagi before the 2011 Tohoku-oki earthquake (M w 9.0).…”
Section: Introductionmentioning
confidence: 99%